Treatable Hyperkinetic Movement Disorders Not to Be Missed - Méneret, Aurélie; Garcin, Béatrice; Frismand, Solène; Lannuzel, Annie; Mariani, Louise-Laure; Roze, Emmanuel (Frontiers in Neurology, 2021)
Hyperkinetic movement disorders are characterized by the presence of abnormal involuntary movements, comprising most notably dystonia, chorea, myoclonus, and tremor. Possible causes are numerous, including autoimmune disorders, infections of the central nervous system, metabolic disturbances, genetic diseases, drug-related causes and functional disorders, making the diagnostic process difficult for clinicians. Some diagnoses may be delayed without serious consequences, but diagnosis delays may prove detrimental in treatable disorders, ranging from functional disabilities, as in dopa-responsive dystonia, to death, as in Whipple's disease. In this review, we focus on treatable disorders that may present with prominent hyperkinetic movement disorders.